Identification of Novel miRNAs Involved in Cardiac Repair Following Infarction in Fetal and Adolescent Sheep Hearts - Lock, Mitchell C.; Tellam, Ross L.; Darby, Jack R. T.; Soo, Jia Yin; Brooks, Doug A.; Seed, Mike; Selvanayagam, Joseph B.; Morrison, Janna L. (Frontiers in Physiology, 2020)
Aims: Animal models have been used to show that there are critical molecular mechanisms that can be activated to induce myocardial repair at specific times in development. For example, specific miRNAs are critical for regulating the response to myocardial infarction (MI) and improving the response to injury. Manipulating these miRNAs in small animal models provides beneficial effects post-MI; however it is not known if these miRNAs are regulated similarly in large mammals. Studying a large animal where the timing of heart development in relation to birth is similar to humans may provide insights to better understand the capacity to repair a developing mammalian heart and its application to the adult heart. Methods: We used a sheep model of MI that included permanent ligation of the left anterior descending coronary artery. Surgery was performed on fetuses (at 105 days gestation when all cardiomyocytes are mononucleated and proliferative) and adolescent sheep (at 6 months of age when all cardiomyocytes contribute to heart growth by hypertrophy). A microarray was utilized to determine the expression of known miRNAs within the damaged and undamaged tissue regions in fetal and adolescent hearts after MI. Results: 73 miRNAs were up-regulated and 58 miRNAs were down-regulated significantly within the fetal infarct compared to remote cardiac samples. From adolescent hearts 69 non-redundant miRNAs were up-regulated and 63 miRNAs were down-regulated significantly in the infarct area compared to remote samples. Opposite differential expression profiles of 10 miRNAs within tissue regions (Infarct area, Border zone and Remote area of the left ventricle) occurred between the fetuses and adolescent sheep. These included miR-558 and miR-1538, which when suppressed using LNA anti-miRNAs in cell culture, increased cardiomyoblast proliferation. Conclusion: There were significant differences in miRNA responses in fetal and adolescent sheep hearts following a MI, suggesting that the modulation of novel miRNA expression may have therapeutic potential, by promoting proliferation or repair in a damaged heart